Investigating Teacher’s Sense of Humor in Indonesia - Tunnisa, Dzakia; Mahmud, Murni; Salija, Kisman (International Journal of Language Education, 2019)
This study investigates the use of humor in teaching English in an English course in Indonesia. It aimed to find out the kinds of humor employed by the teacher and to explore the students’ perspectives toward it. This study employed a qualitative research design and focused on one English course in Makassar, Indonesia. One teacher and one class consisting of seven students were taken as respondents. Data collections relied on observation and interview. Five meetings of classroom interaction were observed and recorded. Seven students from the class were also interviewed deeply. The recordings were transcribed and analyzed based on the framework of Wanzer & Frymier (1999). Findings show that there are some kinds of humor that were employed by the teacher in teaching, namely related humor, unrelated humor, self-disparaging humor, and unplanned humor. New kinds of humor were also found namely unresponded humor and remind humor. Those kinds of humor were proved to give benefits in English language teaching process. The teacher who employed humor in teaching English made the students easy to get the knowledge. Teacher’s humor reduced tension, made the students more comfortable in the teaching-learning process, created good interactions, led to more enthusiastic teaching-learning process, encouraged students’ attendance, and reduced the number of students who felt sleepy in the class. Findings from this study provide significant input for teachers to create effective interaction between teachers and students in English language teaching in Indonesia.